5 - Detention without Trial, Deportation and Security among the Kuria of Tanzania, 1960s–1990s - Iddy Ramadhani Magoti (Afrika Zamani, 2022)
During the colonial and postcolonial periods, African states, including Tanzania, introduced detention without trial and deportation of some people as a strategy for maintaining peace and security. The assumption was that detainees and deportees threatened peace in their respective areas, that their detention and deportation would bring peace and stability, and that eventually they would change their behaviour and become good citizens. To respond to this perceived threat, the colonial and postcolonial governments enacted laws at different intervals from the 1920s to the 1990s. Several people were detained and deported in Tanzania under these laws. Using archival sources, documentary review, newspapers and oral information, this article examines the extent to which detention and deportation helped to maintain peace and security as well as change the behaviours of those who were detained and deported among the Kuria in Tanzania. It argues that the detention and deportation strategy created a peaceful environment temporarily but rarely changed the behaviour of the deportees and detainees. Unlike other places where detention and deportation were used to silence political elites who opposed the existing regimes, the detention and deportation strategy among the Kuria mainly targeted notorious cattle raiders whose undertakings instigated inter-clan conflicts. ‘Tunakuweka Kizuizini kwa Usalama wako na Usalama wa Taifa’ (We detain you for your security and the security of the nation)